Necroptosis contributes to methamphetamine-induced cytotoxicity in rat cortical neurons. (September 2016) - Xiong, Kun; Liao, Huidan; Long, Lingling; Ding, Yanjun; Huang, Jufang; Yan, Jie
Abstract: Necroptosis, a programmed necrosis, is involved in various types of neurodegenerative diseases. In this study, we investigated whether necroptosis contributed to neuronal damage in a methamphetamine injury model.Methods : Primary cultures of embryonic cortical neurons from Sprague-Dawley rats were subjected to different doses of methamphetamine with/without pre-treatment with a specific necroptosis inhibitor, Necrostatin-1. Necrosis was assessed by determining lactate dehydrogenase release and by Annexin V/propidium iodide double staining, while the neuronal ultra-structure was examined by electron microscopy. Tumor necrosis factor-α protein levels were determined by enzyme-linked immunosorbent assay.Results : At early stages (12 h) of post-treatment with methamphetamine, significant necrosis occurred and the viability of neurons decreased in a dose- and time-dependent manner in this model of acute neuronal injury. Pretreatment with Necrostatin-1 led to significant neuronal preservation compared with the methamphetamine-treated groups. Furthermore, tumor necrosis factor-α expression increased in a dose-dependent manner following methamphetamine exposure.Conclusion : Methamphetamine induced necrosis in rat cortical neurons in vitro, both time and dose dependently, and necroptosis may be an important newly identified mode of cortical neuronal death caused by single high-dose methamphetamine administration. Highlights: Methamphetamine can induce necrosis in rat cortical neurons in time- and dose-dependent manner in vitro. Necrostatin-1 targeted a necroptotic pathway in METH-induced neurotoxicity in vitro . Necroptosis may be an important, novel emerging mode of neurons death induced by methamphetamine.